Usefulness of CSF C-Reactive Protein in Differentiating Pyogenic and Aseptic Meningitis (TAJ: Journal of Teachers Association, 2010)
A cross sectional study was done about usefulness of CSF- C reactive protein determining the sensitivity, specificity and predictive value of CSF C-reactive protein estimation. The study was conducted in all the Pediatric unit of Rajshahi Medical College Hospital from March 2008 to July 2009. A total of 130 suspected case of meningitis patients were included in the study. Cerebrospinal fluid culture and C-reactive protein were done for all the patients. Among them 102 were diagnosed as meningitis and 28 were other than meningitis. They were diagnosed as febrile convulsion, seizure disorder, IVH, Among these diagnosed as meningitis, CSF culture were positive in 66 patient and CSF C-reactive protein were positive in 59 patients. Sensitivity and specificity of CSF C-reactive protein were 89.39% and 100% respectively. Predictive value of positive and negative test for CSF-CRP was 100% and 83.72%. DOI: 10.3329/taj.v22i1.5021 TAJ 2009; 22(1): 78-81